Navigating Diversity: Process-Focused Differentiation Through Project-Based Learning in English Classrooms Under the School Zoning System - Nadiya Rachmaudina Liqoiriyin Agus; Anam Sutopo (Departemen Bahasa dan Sastra Indonesia dan Daerah, 2026)
This paper examines the techniques of English teachers in conducting process-focused Differentiated Instruction using a Project-Based Learning approach in zoning-based English classrooms. The introduction of the zoning system has increased heterogeneity among the classrooms, where teachers need to manage issues such as students' varying English proficiency levels, motivation, readiness, participation, and self-confidence. This paper employs a qualitative research design where two English teachers at one public senior high school in Kartasura are involved as participants. Data were collected through semi-structured interviews, classroom observations, and lesson plan analysis. The study revealed three major findings. First, English teachers implemented several process-focused differentiation practices, including heterogeneous grouping, differentiated task distribution, flexible pacing, scaffolding, continuous monitoring and feedback, collaborative learning, and student autonomy. Second, the implementation of process-focused differentiated instruction in the classroom faced several challenges, such as varying levels of English proficiency, difficulties in addressing diverse learning needs, low student motivation and readiness, unequal participation in group work, and differences in students' confidence. Third, teachers addressed these challenges through adaptive strategies, including scaffolding, task differentiation, flexible instruction, active monitoring, direct intervention, and constructive classroom interaction.